Fight for Centrality and Self-management of Space. The Movement of Occupants and Tenants in Buenos Aires - Díaz Parra, Ibán (2016)
The Movement of Occupants and Tenants (MOI by its Spanish acronym) is currently one of the best examples of the revindication of the right to the city in Buenos Aires, as well as the capacity of grassroots organizations to create and re-create the urban space. The struggle of the Movement in this city has characterized for the revindication of the permanence of the popular sectors in the central areas, in a context where these spaces are being revaluated and, urban development projects targeting the urban renewal with clear neoliberal orientation are being designed. This article, which starts from fieldwork carried out with cooperative housings that make up the organization, presents the dispute for the urban centre between the capital and grassroots organizations paying attention to both, the material fight specifically for high demanded land, and the ideological struggle for legitimacy of the different uses and ways of life in the central spaces.